Chasing World-Class Urbanism Global Policy versus Everyday Survival in Buenos Aires - Lederman, Jacob (Globalization and community ;, 2020)
Questions increasingly dominant urban planning orthodoxies and whether they truly serve everyday city dwellers. What makes some cities world class? Increasingly, that designation reflects the use of a toolkit of urban planning practices and policies that circulates around the globe. These strategies--establishing creative districts dedicated to technology and design, "greening" the streets, reinventing historic districts as tourist draws--were deployed to build a globally competitive Buenos Aires after its devastating 2001 economic crisis. In this richly drawn account, Jacob Lederman explores what those efforts teach us about fast-evolving changes in city planning practices and why so many local officials chase a nearly identical vision of world-class urbanism. Lederman explores the influence of Northern nongovernmental organizations and multilateral agencies on a prominent city of the global South. Using empirical data, keen observations, and interviews with people ranging from urban planners to street vendors he explores how transnational best practices actually affect the lives of city dwellers. His research also documents the forms of resistance enacted by everyday residents and the tendency of local institutions and social relations to undermine the top-down plans of officials. Most important, Lederman highlights the paradoxes of world-class urbanism: for instance, while the priorities identified by international agencies are expressed through nonmarket values such as sustainability, inclusion, and livability, local officials often use market-centric solutions to pursue them. Further, despite the progressive rhetoric used to describe urban planning goals, in most cases their result has been greater social, economic, and geographic stratification. Chasing World-Class Urbanism is a much-needed guide to the intersections of culture, ideology, and the realities of twenty-first-century life in a major Latin American city, one that illuminates the tension between technocratic aspirations and lived experience.